2008
DOI: 10.1007/s10658-008-9321-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between resistance to pine wilt disease and the migration or proliferation of pine wood nematodes

Abstract: To study the relationship between resistance to pine wilt disease and the migration or proliferation of pine wood nematodes (PWN) (Bursaphelenchus xylophilus), we conducted experiments using clonallypropagated Japanese black pines (Pinus thunbergii) with pre-evaluated individual resistance levels. Bark including the cortical resin canals-one of the main migration pathways of PWN-was removed by girdling, but neither the migration of PWN nor symptom development of pine wilt disease were inhibited by this treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Similar histological features were reported for the Asiatic susceptible pine species (e.g. P. thunbergii, P. densiflora) [2,3,4]. The wilting process of PWD has been explain, at least in part, by water deficit induced by nematodes pathological cavitation.…”
supporting
confidence: 74%
“…Similar histological features were reported for the Asiatic susceptible pine species (e.g. P. thunbergii, P. densiflora) [2,3,4]. The wilting process of PWD has been explain, at least in part, by water deficit induced by nematodes pathological cavitation.…”
supporting
confidence: 74%
“…In a previous experiment using stem cuttings (Mori et al, 2008), the difference in the number of PWN between 1200 I 900 'S 600 , Bursaphelenchus xylophilus, detected in the bioassay that were co-cultured with methanol extract-loaded paper disks. Numbers of PWN were counted 3 days after inoculation.…”
Section: Discussionmentioning
confidence: 93%
“…A common observation among these studies was that significantly fewer PWN were detected in resistant pines than in susceptible ones, suggesting that resistance factors were involved in inhibiting migration or proliferation of PWN. In particular, we demonstrated that symptom development in pine trees was unaffected by inhibiting or facilitating PWN migration, and that the PWN population drastically increased in susceptible pine stem cuttings but not in resistant ones (Mori et al, 2008). We concluded that it was likely that resistance was dependent on factors that inhibited PWN proliferation rather than their migration.…”
mentioning
confidence: 74%
“…This hypothesis was based on crosssectional observations of the main migration pathways, i.e., cortical resin canals [21]. However, our previous study demonstrated that symptom development in pine trees was unaffected by mimicking inhibited or free PWN migration [22]. This suggested that resistance was independent of PWN migration.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that resistance was independent of PWN migration. The PWN population drastically increased in susceptible pine stem cuttings by 20 days after inoculation (dai), while it remained unchanged or gradually decreased in resistant cuttings [22]. Thus, it is likely that resistance depends on factors that inhibit the proliferation of PWN, rather than migration.…”
Section: Introductionmentioning
confidence: 99%